The influence of perception of school principal’s leadership on teachers’ job satisfaction in the interior of Sabah, Malaysia: a case study in Beaufort - Men, Ye Chong; Kasim Mansur; Yew, Joe Ho (Springer Singapore, 2014)
This study investigates the relationship between the leadership perceptions of school principal among the teachers and their job satisfaction in a multiethnic semi-rural area in the interior of Sabah namely Beaufort. Results of the research showed that there is a significant positive relationship between the perceived leadership of school principal and the job satisfaction among the teaching staffs and such relationship is not influenced by the demographic attributes of the sample. The results accentuate the importance developing the leadership of principals in public schools to enhance the teaching staffs' commitment and job satisfaction that indirectly impact the overall performance schools and students.